Problem Penyembuhan Reiki Perspektif Al-Ghazali - Jarman Arroisi; Agus Dwi Saputro (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
Reiki as a soul healing technique originates from Buddhism, contains basic problems even though it has been widely accepted by society. This technique was rediscovered by Mikao Usui and continues to grow today. In the perspective of Islamic psychiatric healing, through Imam Al-Ghazali, soul healing can be done by means of riyadhah and several other interconnected methods. Riyadhah, this psychological healing trains the soul with spiritual values and is connected with God. This study aims to uncover the problems of reiki techniques that have been applied, then demonstrate the concept of healing in Islam according to Imam Al-Ghazali. This research is a qualitative literature research with a historical approach. The primary sources used were writings from reiki practitioners, and responded by using methods according to Imam Al-Ghazali, one of which was riyadhah. The results of the research show that: First, reiki as a healing method contains Buddhist values, this is confirmed by the principles, the basis that forms the practice of reiki. Second, psychological healing in the Islamic realm can use several methods from Imam Al-Ghazali, including riyadhah, a technique based on faith and sharia.